Chingaza : territorio resiliente : atlas textil inspirado en PNN Chingaza (2018)
This proyect "Chingaza: Textile Atlas" is a textile collection that comes from an exploration of the Chingaza Natural National Park in Colombia. The place was explored by psicogeography metodology and each one of the pieces is a personal material exploration of the sensations and emotions that the places transmits to me. The collection is made of three pieces and each one of them represents different elements of the territory, these are: Water, earth and air.